Relationships of the Trace Elements Zinc and Magnesium With Diabetic Nephropathy-Associated Renal Functional Damage in Patients With Type 2 Diabetes Mellitus - Feng, Jianan; Wang, Heyuan; Jing, Zhe; Wang, Yue; Wang, Wanning; Jiang, Yanfang; Sun, Weixia (Frontiers in Medicine, 2021)
Zinc (Zn) and magnesium (Mg) are essential trace elements in humans. Their deficiency may be associated with inflammation and oxidative stress (OS) in patients with diabetic nephropathy (DN), but the mechanisms involved have not been fully characterized. We aimed to investigate the relationships between circulating concentrations of Zn and Mg and pro-inflammatory factors with DN-associated renal functional damage in patients with type 2 diabetes mellitus (T2DM). To this end, we studied 20 healthy people, 24 patients with T2DM, and 59 patients with T2DM and T2DN. Serum and urine Zn and Mg concentrations were measured using the 2-(5-nitro-2-pyridylazo)-5-(N-propyl-N-sulfopropylamine) phenol (nitro-PAPS) chromogenic method and the xylidyl blue method, respectively, and the circulating concentrations of pro-inflammatory cytokines (interleukin (IL)-1β, IL-6, IL-8, IL-10, IL-12, and tumor necrosis factor-α (TNF-α)) were measured using flow cytometry. The serum concentrations of Zn and Mg were significantly lower in patients with T2DM and DN than in healthy controls. Serum Zn, urine Zn, and urine Mg concentrations decreased, while those of IL-6 and IL-8 increased with the progression of DN-associated renal functional damage. Furthermore, the serum and urine Zn concentrations negatively correlated with the serum IL-6 and IL-8 concentrations. Notably, the serum Zn concentration was found to independently protect against DN in patients with T2DM. Hypozincemia may be associated with the T2DN-associated renal functional damage because it exacerbates inflammation.